2022
DOI: 10.1080/13625187.2022.2093851
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, professional attitudes, and training among health professionals regarding male contraceptive methods

Abstract: Objectives: Health professionals are at the forefront of information and acceptability regarding contraceptive methods, however only one study evaluated their knowledge of male contraception (MC) including hormonal MC (HMC) and thermal MC (TMC). Our objective was to evaluate the knowledge, professional attitudes, and training of French practitioners regarding the management of couple contraception by male contraception (MC). Study design: We designed a descriptive, cross-sectional, multicentre study in 2,396 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A recent systematic review of barriers to male participation in general reproductive health care highlighted that barriers to inclusive and integrated quality reproductive health services are the primary limitation to male engagement in reproductive health, and pointed to health care workers as a major contributor to the lack of access to reproductive health services ( Roudsari et al , 2023 ). Another recent study similarly highlighted that many health professionals involved in contraception have unsatisfactory knowledge of male contraceptive methods and are not reliably offering male options during couple contraceptive counseling sessions ( Tcherdukian et al , 2022 ). Measuring the impact of provider bias poses major methodological challenges, but several studies have shown that provider bias has a significant impact on provider contraceptive provision practices and may lead to reduced contraceptive access ( Solo & Festin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of barriers to male participation in general reproductive health care highlighted that barriers to inclusive and integrated quality reproductive health services are the primary limitation to male engagement in reproductive health, and pointed to health care workers as a major contributor to the lack of access to reproductive health services ( Roudsari et al , 2023 ). Another recent study similarly highlighted that many health professionals involved in contraception have unsatisfactory knowledge of male contraceptive methods and are not reliably offering male options during couple contraceptive counseling sessions ( Tcherdukian et al , 2022 ). Measuring the impact of provider bias poses major methodological challenges, but several studies have shown that provider bias has a significant impact on provider contraceptive provision practices and may lead to reduced contraceptive access ( Solo & Festin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%